Uso da ferramenta Dynamo para geração automática de estruturas de galpões - Santos, Narliane Silva dos (Brasil, 2023)
The BIM (Building Information Modeling) methodology makes it possible to integrate data and manage information, optimizing engineering projects and reducing time and costs even in the project phases. Because of this, the civil engineering sector is increasingly looking for tools that apply this methodology, ensuring greater control of schedules, costs and material consumption in the development and execution of projects. This monograph presents a study on the interoperability between Dynamo and Revit software with the objective of performing the automatic modeling of metallic industrial shed structures constituted by solid core profiles, applying some of the BIM concepts and also a visual programming method. The geometric and structural configurations were, in addition to the application of materials, developed in the Dynamo program, extracting data from the Revit library for the insertion of metallic profiles. The Dynamo program allows the execution of a computational routine that was developed in the present work and resulted in the automatic modeling of shed structures with a gable plan. Through application examples, the potential application of the Dynamo software in the elaboration of structural projects is demonstrated, especially in cases that involve repetitive patterns.